AI: Apakah Guru Masih Punya Peran di Masa Depan - Regita Amalia Septiani; Alifia Nasfa Ramadani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The advancement of artificial intelligence (AI) has significantly impacted education, particularly in providing personalized learning and administrative efficiency. However, questions arise about whether the teacher's role remains relevant in this technological era. This study aims to examine the role of teachers in the context of AI development through a literature review method, analyzing previous research on AI integration in education. The findings reveal that while AI excels in data processing and adaptive learning, teachers maintain an irreplaceable role in building emotional connections, instilling moral values, and guiding students' character development. Teachers also act as mentors who provide motivation and facilitators who create interactive learning environments. These findings highlight the importance of collaboration between AI and teachers to create more inclusive and effective education. Therefore, AI should be seen not as a replacement but as a tool to enhance the teacher's role in fostering holistic student development.